Utilization of Puskesmas in Efforts to Prevent COVID-19 in Bengkulu City - Oktarianita Oktarianita; Andry Sartika; Nopia Wati; Bintang Agustina Pratiwi (Universitas Ahmad Dahlan, 2021)
Background: Puskesmas as First Level Health Facilities (FKTP) plays a vital role during the Covid-19 pandemic in preventing and controlling the number of Covid-19 cases by anticipating, detecting, responding to events. However, at this time, the puskesmas are still underutilized by the community. The highest confirmed positive cases in Bengkulu City were in the Gading Cempaka District, with 990 cases. This study aimed to determine the variables related to the utilization of puskesmas in Bengkulu City. Methods: This research was quantitative research with a cross-sectional study design. Data collection was carried out by distributing questionnaires to respondents using an accidental sampling technique executed in March-August 2021. The research population was the entire community of Bengkulu City, with a sample of 110 respondents from the Gading Cempaka District, Bengkulu City. Data were analyzed by univariate to multivariate logistic regression. Results: The results show that 88 respondents (78.2%) have utilized the puskesmas, as many as 86 (78.2%) were female, 86 respondents (60.9%) belonged to the young age group, respondents with higher education were 73 respondents ( 66.4%), 73 respondents (66.4%) worked and as many as 79 respondents (71.8%) have income <UMP. The bivariate analysis results showed that the factors related to the utilization of the puskesmas (p<0.05) were variables of age, education, occupation, and income despite no relationship between gender, distance, knowledge, and family support (p>Î±). The results of the multivariate analysis showed that education was the dominant factor influencing the utilization of the puskesmas with (p-value = 0.010; B = 2.707; 95% CI = 1.892-118.569). Conclusion: The community has taken advantage of the puskesmas in terms of preventing Covid-19. The utilization of puskesmas is affected by age and education level.